Patient-reported outcome measures following surgeries in implant dentistry and associated factors: a cross-sectional study - Xinyu Wu; Qi Yan; Bin Shi; Mengjie Ye; Jiahui Sun; Haibin Xia (BMJ Open)
Objectives We aimed to evaluate the patient-reported outcome measures (PROMs) of dental implant surgeries and analyse the associated indicators.Design A cross-sectional study design was used.Setting Department of Oral Implantology, Hospital of Stomatology, Wuhan University (May 2020–April 2021).Participants Participants with missing teeth in need of implant-supported rehabilitation.Interventions Dental implant placement and/or bone augmentation procedures.Primary and secondary outcome measures The primary outcome was discomfort on postoperative day 1, measured using a numerical rating scale (NRS). Secondary outcomes included pain and anxiety during surgery; discomfort on postoperative days 3, 7 and 14; and post-surgical complications.Results A total of 366 participants were included, of which 288 (78.7%) and 328 (89.7%) reported no to mild pain and anxiety (NRS 0–3) during surgery, respectively. The proportion of patients reporting discomfort decreased from postoperative day 1 (57.7%) to day 3 (36.1%) and day 7 (17.5%). The most frequent postoperative adverse events were pain and swelling. Patient-related factors (age, sex, smoking, alcohol consumption, history of periodontitis, and pain and anxiety during surgery) and surgery-related factors (type and extent of surgical procedure) were analysed. The factors associated with the severity of discomfort after surgery included alcohol consumption, pain perception during surgery, bone augmentation procedures and age (p<0.05). Similarly, the factors associated with the duration of discomfort included alcohol consumption, pain perception during surgery and age (p<0.05).Conclusions PROMs related to dental implant surgeries can be predicted using certain risk indicators. Alcohol consumption, pain during surgery and age were associated with discomfort following dental implant surgery.